Contaminant rejection in the presence of humic acid by membrane distillation for surface water treatment - Han, Le (2017)
Membrane distillation (MD) is a promising means for high-purity separations like that needed for potable water. The benefits of MD have not been realized for the treatment of surface or ground water, whereby the presence of both humic acid and calcium are detrimental to other membrane-based processes. Accordingly, this study investigated the efficacy of MD in rejecting various contaminants, namely, ibuprofen, boron and arsenic, in the presence of typical feeds comprising humic acid, calcium chloride and sodium chloride. Feeds investigated ranged from DI water to synthetic feeds mimicking surface water to NEWater brine. Results consistently indicate constant permeate fluxes and low conductivities throughout the experiments with varying concentrations of humic acid and calcium, along with varying pH values, which implies negligible membrane fouling and wetting. Also, complete rejections of boron and arsenic were achieved, while rejection of ibuprofen was approximately 90%. The detection of the non-volatile ibuprofen and humic acid in the permeate suggests some hydrophobic interactions with the membrane. Finally, a cost analysis was carried out to evaluate MD against the conventional nanofiltration (NF) process. Although MD is currently at a higher cost than NF, (i) the availability of improved membranes tailored for MD and low-cost heat would depress costs to at least that of NF, and (ii) the performance of MD is superior in terms of sustained flux over prolonged periods, capacity to treat feeds with higher concentrations of foulants, and better permeate quality.